ICT in University: How Lecturers Embrace Technology for Teaching - Aminatun, Dyah (STKIP Muhammadiyah Pringsewu, 2019)
Current era demands educators to deal with technology. Seeing that most students of university are supported with abundant facilities in learning nowadays, lecturers need to get familiar with current issues and technologies to encounter it. Role of Information and Communication Technology (ICT) in pedagogy will facilitate lecturers in teaching and learning process as well as improving their professionalism. It is a qualitative research with fifteen lecturers as the sample of research. The result shows that although all lecturers have used ICT for teaching, they apparently still need traditional medium such as whiteboard since ICT is also lack in some parts. Keywords: ICT, teaching technology, teaching media